PENGEMBANGAN SMART BRANDING PERKOTAAN DALAM PELAYANAN KEPARIWISATAAN KOTA MAKASSAR - inriana, Alikha; Mahsyar, Abdul; Hawing, Hardianto (Universitas Muhammadiyah Makassar, 2023)
The purpose of this study is to find out the strategy carried out by the Tourism Office in developing Makassar city smart branding. Data collection techniques used are observation, interviews, and documentation. The results of this study indicate that in an effort to develop Makassar city smart branding. This process shows that every strategy undertaken, starting from publications, events, news, community involvement, informing of image, lobbying and negotiation, and social responsibility, has been carried out jointly by the city government and the community. In each strategy, show participatory or planning that involves the community because in this strategy the community is given understanding and knowledge related to tourism in order to create a more qualified young generation by seeing the potential, opportunities and problems that will be faced by the community.